An investigation of ring and dicentric chromosomes found in three Turner's syndrome patients using DNA analysis and in situ hybridisation with X and Y chromosome specific probes. Issue 1 (January 1991) - Cooper, C; Crolla, J A; Laister, C; Johnston, D I; Cooke, P
Abstract : We have studied three patients with features of Turner's syndrome, two with a 45, X/46, X, r(?) and the third with a 45, X/46, X, dic?(Y) karyotype. Because Turner's syndrome patients with a mosaic karyotype containing a Y chromosome are known to have a high risk of developing gonadal tumours, we used DNA analysis and in situ hybridisation with X and Y specific probes to identify the chromosomal origin of the rings and dicentric chromosomes in the three index patients. Both ring chromosomes were shown to be of X origin, while the dicentric was composed of Y chromosome material. We discuss the importance of using a combination of molecular and cytogenetic analyses in such cases.